The types of comorbidities are associated with self-care of heart failure, but not the number of comorbidities. (29th July 2021) - Lee, KS; Moser, DK; Dracup, K
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): RO1HL083176 Improving Self-Care Behavior and Outcomes in Rural Patients with Heart Failure Background/Introduction: Patients with heart failure (HF) experience cardiac and non-cardiac related comorbid conditions. Such comorbidities create challenges to successful engagement in self-care of HF because patients are asked to simultaneously perform a variety of recommended self-care activities for HF and their comorbid conditions. It is possible that patients with a greater number of comorbid conditions experience more difficulty performing activities of HF self-care compared to those with a smaller number of comorbid conditions. However, it is also possible that types of comorbid conditions are more important factors influencing self-care of HF. Purpose: To explore whether self-care of HF is associated with the number of comorbid conditions or types of comorbid conditions. Methods: A total of 589 patients with HF (66 years, 41% female, 65% NYHA III/IV) were included in this study. The number of comorbid conditions was measured using the list of the conditions in the Charlson Comorbidity Index. Types of comorbidities were defined as follows: concordant conditions, sharing overall pathophysiologic risk profiles with HF, and discordant conditions, not being directly related to HF. Patients were categorized into 4 groups: HF patients without comorbidities; those with concordant conditions; those with discordant conditions; and those with both concordant and discordant conditions. Self-care was measured with the European HF self-care behavior scale. A multivariate linear regression was performed to explore the relationship of HF self-care with the number and types of comorbid conditions after adjusting for relevant covariates. Results: The number of comorbid conditions was not associated with self-care of HF. However, the types of comorbid conditions were related to self-care of HF after controlling for covariates. Compared to HF patients without comorbidities, patients with both concordant and discordant conditions were more likely to have poorer self-care (β=0.155, 95% CI 0.29-4.09). However, levels of self-care in patients having either concordant or discordant conditions were not different from levels in patients having no comorbid conditions. Conclusion: Patients' adherence to HF self-care was associated with the types of comorbidities, but not the simple count of comorbidities. Patients who had both concordant and discordant conditions were more likely to perform poor self-care of HF compared to those who had either concordant or discordant conditions or no comorbid conditions. It appears that HF patients with both concordant and discordant conditions experience difficulty integrating HF self-care in relation to a variety of conditions.